Development of Soft Tactile Sensor for Prostatic Palpation Diagnosis: Sensor Structure Design and Analysis - Zhongwei Jiang; Seiji Chonan; Yoshikatu Tanahashi; Takuji Kato; Mami Tanaka (Shock and Vibration)
This paper is concerned with the development of a palpation probe for assessment of prostatic cancer and hypertrophy. The sensor is constructed by layering two polivinylidene fluoride (PVDF) films into soft material layers such as vulcanized rubber and sponge rubber sheets. Since the contact condition between the sensor and soft objects influences the sensor output significantly, the improvement of its sensitivity is investigated by design of an attachment covered over the sensor surface. In this report, the theoretical model of the sensor and the design of the attachment are presented and the attachment is validated for soft substances due to experimental investigation. Finally, a compact probe developed for clinical testing is presented and the data obtained from the patients are treated by the wavelet transform for de-noising. Some representative clinical data show that the sensor could be a useful tool for group medical checkup on prostatic cancer and hypertrophy.